Smart Lighting Operation for The Growth of Bird's Eye Chili Plants Using Arduino Uno - Supandri, Muhammad Hamdu; Wirateruna, Efendi S; Basuki, Bambang Minto (Jurnal Teknik Elektro dan Informatika, 2024)
Unfavorable weather conditions, climate change, and pests can disturb chili cultivation. The "Prototype for Artificial Lighting Operation for the Growth of Chili Plants (Capsicum Frutescens L) Based on Arduino Uno" is designed to help farmers who lose land or experience crop failure due to unpredictable weather, which prevents plants from receiving optimal sunlight. Here, the researcher utilizes Arduino Uno in the control system to process data and determine the values obtained from the system. The light sensor (BH1750) detects light radiation (lux), and the temperature sensor (DS18B20) detects temperature (°C). White daylight LEDs are used for lighting. Testing is conducted using the static group comparison method to compare different groups or conditions of each treatment. This research involves creating a prototype of an artificial lighting device based on Arduino Uno, which can display data and control the necessary temperature and lighting. The device is tested thoroughly according to the programmed plan to determine the significance of its impact on the development and growth of chili plants. The results show that the greatest stem height increase occurred in the third treatment, with an average of 0.6 cm per day. However, by the 15th day, the plants tended to slow down, stopping growth on the 38th day and starting to turn yellow on the 40th day. The greatest branch increase occurred in the second treatment (using the device with the door open), with an average of 2 branch nodes per day.